Chiral inversion mutagenesis identifies geometrically constrained residues within self-associating low-complexity domains - Ryan L. Beckner; Lily Kim; Christien Carter; Abby Walterscheid; Glen Liszczak (Proceedings of the National Academy of Sciences, 2026)
Many protein low-complexity domains (LCDs) self-associate to enable cellular function, yet fundamental questions remain regarding how polypeptide chemical and structural features beyond side chain identity contribute to LCD–LCD interactions. For instance, the folds adopted by globular proteins emerge from constraints enforced by homochirality of genetically encoded polypeptides. However, it remains unclear to what extent similar geometric constraints apply to LCD self-association. Herein, we use protein total and semi-synthesis to probe the contribution of C α stereochemistry to LCD self-association with synthetic Chiral Inversion Mutagenesis (ChIM). By introducing targeted L-to-D amino acid inversions, ChIM identifies C α stereocenters under geometric constraint without modification of side-chain functionalities. We apply ChIM to the LCDs of inner nuclear lamina protein Emerin and neurofilament light chain and find that chiral inversion produces strongly position-dependent effects upon LCD self-association. Our study describes essential structural features that enable LCD self-association and chemical strategies to interrogate LCD biochemistry.